Design and experiment of light angle adjustable device for measuring sugar content of citrus by near infrared spectroscopy - ZENG Xianming; HAN Longbo; WEN Tao; DAI Xingyong (Shipin yu jixie, 2023)
Objective: To solve the problem of insufficient spectral information obtained by the fixed illumination angle of the near-infrared spectroscopy to detect the sugar content of fruits. Methods: A light angle adjustable device for the diffuse transmission near-infrared spectroscopy was designed to detect the sugar content of citrus based on the simplified model of the remote motion center of the light source. The device had carried out the structural performance analysis and the test of the citrus sugar under different illumination angles. Results: The adjustment range of the light angle of the device was set to 0°~60°. The displacement deviation between the center of the four light sources and the bullseye was the smallest （7.5 mm） at 60°. Under different illumination angles, the error between the average illumination angle of light source 2, 3 and 4 and the reference value of light source 1 was within 1°. When the illumination angle was 30°, the citrus sugar prediction model based on the original transmittance spectrum data had the best effect. At this time, the correlation coefficient of the prediction set, the root mean square error of the prediction set, the correlation coefficient of the correction set, and the root mean square error of the correction set were 0.887 6, 0.897 5, 0.456 0, 0.430 9 °Brix, respectively. Conclusion: The developed near-infrared spectroscopy detection device can automatically synchronize and adjust the angle of illumination of four light sources to align with the center of the fruit.